Craniofacial and dental manifestations in Dubowitz syndrome - case report - Santos, Pedro Paulo de Andrade (2009)
Dubowitz is a rare genetic disorder involving dental and craniofacial abnormalities, growth and mental retardation. This includes a variable phenotype with many manifestations as well as craniofacial, ocular, dental, cutaneous, gastro-intestinal, skeletal, cardiovascular, urogenital, neurological and behavior problems. The craniofacial and dental characteristics have been diagnosed; however, there has been no publication of this description. The objective of this report was to show the importance of recognition, and clarify the peculiar characteristcs of a patient with Dubowitz syndrome.